2004
DOI: 10.1091/mbc.e03-11-0786
|View full text |Cite
|
Sign up to set email alerts
|

Different Gene Expression Patterns in Invasive Lobular and Ductal Carcinomas of the Breast

Abstract: Invasive ductal carcinoma (IDC) and invasive lobular carcinoma (ILC) are the two major histological types of breast cancer worldwide. Whereas IDC incidence has remained stable, ILC is the most rapidly increasing breast cancer phenotype in the United States and Western Europe. It is not clear whether IDC and ILC represent molecularly distinct entities and what genes might be involved in the development of these two phenotypes. We conducted comprehensive gene expression profiling studies to address these questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
360
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(382 citation statements)
references
References 65 publications
19
360
0
3
Order By: Relevance
“…In general, the findings for ductolobular tumours were more similar to ductal than to lobular tumours. These findings are consistent with a recent gene expression study (Zhao et al, 2004), which found that about half of the lobular cancers had similar gene expression patterns to ductal tumours, while the remaining 'typical' lobular cancers had a different gene expression pattern. However, in these analyses we found little evidence that these reproductive factors act differently on either ductal or lobular tumours, with the possible exception that early age at first birth was most strongly associated with lower risk of lobular cancers, and that ductolobular tumours were associated with the strongest risk reduction per full-term pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…In general, the findings for ductolobular tumours were more similar to ductal than to lobular tumours. These findings are consistent with a recent gene expression study (Zhao et al, 2004), which found that about half of the lobular cancers had similar gene expression patterns to ductal tumours, while the remaining 'typical' lobular cancers had a different gene expression pattern. However, in these analyses we found little evidence that these reproductive factors act differently on either ductal or lobular tumours, with the possible exception that early age at first birth was most strongly associated with lower risk of lobular cancers, and that ductolobular tumours were associated with the strongest risk reduction per full-term pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…A shorter latency period of ductal compared to lobular carcinoma obtained from our analysis could be due (at least in part) to higher proliferation and apoptosis [21]. Our results are also in agreement with other molecular studies on cancer proliferation, biology, and genetics, which demonstrated that lobular tumors exhibited similarities to low-grade ductal tumors [22][23][24]. Several studies have revealed a striking similarity between in situ and invasive breast cancers, where all markers correlated with grade rather than with tumor invasiveness [22,[25][26][27], and there was a good concordance between grade in primary and metastatic tumors [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…Microarray-based class discovery studies pioneered by Perou and colleagues [1] have demonstrated that breast cancer could be classified into molecularly distinct groups based upon global gene expression profiles and their similarity to those of normal cell counterparts. Their results have subsequently been confirmed and expanded by multiple independent studies [2][3][4][5]. One of these biologically and clinically distinct groups, which has attracted attention in recent years as a molecularly distinct subtype of breast cancer with poor prognosis, is basal-like cancer [1,3,4,6].…”
Section: Introductionmentioning
confidence: 84%